Design of an Integrated Information System for Regional Property in Indonesia Probolinggo City Government - Akromul Khaidar; Aang Afandi; Jaswadi Jaswadi (Journal of Applied Business, Taxation and Economics Research, 2022)
This study aims to analyze the integrated information system for a regional property in the Probolinggo City government using the concept of Business Process Management notation. The object of research is the government of Probolinggo City. This case study was analyzed to find problems in the research object and the design of procedures when conducting capital expenditures in each government agency. This study uses quantitative methods with resource based theory techniques with several stages ranging from data collection, case identification, and in-depth analysis to theory development and implications for its completion. The result of the research is a business process model based on Business Process Management Notation (BPMN) which can increase effectiveness and efficiency so that it has implications for improving the quality of business processes in Government agencies Related to Capital Expenditures so that they are understood and correct so that they are effective.